Beef Arisan Practices from the Perspective of Sharia Economic Law: A Study in Dusun Jimus - Saniyah, Mila Durrotus; Naachy, Dzin Nun (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. Various community-based economic practices continue to develop in rural areas, including the arisan daging sapi (beef-rotation scheme). This practice is carried out by residents as an alternative method to obtain beef at a more affordable and structured manner. However, the mechanism of payment rotation, price determination, and distribution raises questions regarding its compliance with the principles of Islamic Economic Law, particularly related to gharar, maisir, and fairness of exchange. Aim. This study aims to examine the legal status of the arisan daging sapi practiced in Dusun Jimus, Karanganyar Village, Wates District, Kediri Regency, as viewed from the perspective of Islamic Economic Law. The research focuses on identifying the contract (akad) used, analyzing the presence of prohibited elements, and determining whether the practice aligns with sharia principles. Methods. This research employs a qualitative descriptive method with an empirical juridical approach. Data were collected through observation, in-depth interviews with organizers and participants of the arisan, and documentation related to its implementation. The analysis was conducted through data reduction, classification, interpretation, and drawing conclusions based on the framework of Islamic Economic Law. Results. The findings indicate that the arisan daging sapi in Dusun Jimus generally operates based on mutual agreement and community trust. The practice does not contain elements of maisir and is free from excessive gharar, as payment schemes and distribution schedules are clearly agreed upon. Nevertheless, several weaknesses were identified, including the absence of written agreements and potential price disparities that may affect fairness. Overall, the practice is permissible (mubah) as long as transparency, fairness, and clarity of the akad are consistently maintained.